Metacognitive strategy instruction (MSI) for reading: Co-regulation of cognition - Bromeley Philip,; Tan, Kim Hua (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2006)
This paper aims to show how a teacher and ESL learners can successfully engage in mutual regulation of strategy use as they co-construct meaning from the reading text. It focuses on the teacher’s effort at giving direct explanation of various learning strategies for reading, that is, it illustrates how learners are explicitly taught not only the various components of a learning strategy but also the rationales of the “how”, “when” and “where” to use that particular strategy. The study on co-regulation of strategy use adopts a qualitative approach to data collection and analysis. It was conducted via the implementation of a Metacognitive Strategy Instruction (MSI) for academic reading. The instruction session started with an explicit direct explanation of learning strategies that include macro strategies such as planning, comprehension monitoring, problem solving, evaluating and modifying. Subsequently, the learners were taught how to apply the strategies using a strategic processing framework called Self-regulated Learning Approach to Strategic Learning (SRSL) to construct meanings from the reading text. The qualitative account of the learners’ strategy use was elicited using a qualitative retrospective written recall protocol (RWP). The study found that both the High Proficient (HP) and Low-proficient (LP) learners benefited reasonably well from the experience of the MSI sessions. The learners reported on how the strategies helped facilitate their reading process. The key issue revealed in the study is that the MSI sessions have managed to at least prepare if not transform the learners into becoming metacognitively sophisticated readers